Global Identification of ANTH Genes Involved in Rice Pollen Germination and Functional Characterization of a Key Member, OsANTH3 - Lee, Su Kyoung; Hong, Woo-Jong; Silva, Jeniffer; Kim, Eui-Jung; Park, Soon Ki; Jung, Ki-Hong; Kim, Yu-Jin (Frontiers in Plant Science, 2021)
Pollen in angiosperms plays a critical role in double fertilization, by germinating and elongating pollen tubes rapidly in one direction to deliver sperms. In this process, the secretory vesicles deliver cell wall and plasma membrane materials, and excessive materials are sequestered via endocytosis. However, endocytosis in plants is poorly understood. AP180 N-terminal homology (ANTH) domain-containing proteins function as adaptive regulators for clathrin-mediated endocytosis in eukaryotic systems. Here, we identified 17 ANTH domain-containing proteins from rice based on a genome-wide investigation. Motif and phylogenomic analyses revealed 7 asparagine-proline-phenylalanine (NPF)-rich and 10 NPF-less subgroups of these proteins, as well as various clathrin-mediated endocytosis-related motifs in their C-terminals. To investigate their roles in pollen tube growth, we performed meta-expression analysis of all genes encoding ANTH domain-containing proteins in Oryza sativa (OsANTH genes) in anatomical samples, including pollens, and identified five mature pollen-preferred OsANTH genes. The subcellular localization of four OsANTH proteins that were preferentially expressed in mature pollen suggested their cellular function in the plasma membrane. Of them, OsANTH3 represented the highest expression in mature pollen. A functional characterization of OsANTH3 using T-DNA insertional knockout and gene-edited mutants revealed that a mutation in OsANTH3 decreased pollen germination and seed fertility in rice. Thus, detailed analyses of the phenotypes in the mutant highlight the significance of ANTH in endocytosis during pollen germination in rice.